Complex ultrasound diagnostic assessment of the results of neoadjuvant chemotherapy for locally advanced cervical cancer (Stages IIB–IIIB) - L. A. Ashrafyan; O. I. Aleshikova; N. A. Babaeva; I. B. Antonova; S. V. Ivashina; S. L. Vashakmadze; A. A. Myagkova; T. A. Motskobili (Опухоли женской репродуктивной системы)
Background. Current complex ultrasound diagnosis using novel imaging techniques can assess, to a high accuracy, different tumor parameters during neoadjuvant chemotherapy (NCT) for locally advanced cervical cancer (CC) (Stages IIB–IIB). This assessment is very important and necessary to define further treatment policy.Materials and methods. A total of 199 patients diagnosed with Stages IIB–IIIB CC, including 60 patients with Stage IIB (T2bN0M0), 4 with Stage IIIА (T3aN0M0), and 135 with Stage IIIВ (T2bN1M0, T3aN1M0, T3bN0–1M0) (according to the International Federationof Gynecology and Obstetrics (FIGO) classification), who received NCT at Stage 1 of treatment, were examined. Complex ultrasound study was conducted before treatment initiation and after each NCT cycle. The therapeutic pathomorphism of a tumor was evaluated in surgically treated patients.Results. The criteria have been determined for evaluating the efficiency of NCT for locally advanced CC, which are based on current ultrasonographic techniques including B-mode, Doppler ultrasound (power, spectral, three-dimensional ones), as well as on the results of therapeutic pathomorphism.Conclusion. The criteria for evaluating the efficiency of NCT for CC should be based on current complex ultrasonographic techniques.